PERUBAHAN KOMPOSISI KIMIA DAN AKTIVITAS ANTIOKSIDAN PADA PEMBUATAN TEPUNG DAN CAKE UBI JALAR UNGU (Ipomoea batatas L.) - Rafael Remit Winardi; Healthy Aldriany Prasetyo (Politeknik Pembangunan Pertanian Medan, 2020)
The purpose of this study was to study the antioxidant activity associated with anthocyanin levels during processing of fresh purple sweet potato into flour and cake. Testing the antioxidant activity using the DPPH method (2,2-Diphenyl-2-picrylhidrazil). The results showed that there were significant differences (p <0.05) of the observed parameters. Fresh purple sweet potato is obtained; water content (56.586%), ash content 2.211%), fat content (0.589%), protein content (5.910%), carbohydrate content (34.704%), anthocyanin content (62.138 mg / 100g) and antioxidant activity (59.332%). In purple sweet potato flour obtained; water content (3.510%), ash content (2.404%), fat content (0.334%), protein content (3.933%), carbohydrate content (92.977%), anthocyanin content (20.196 mg / 100 g) and antioxidant activity (50,600% ). In purple sweet potato cake obtained; water content (21.564%), ash content (1.464%), fat content (15.179%), protein content (7.035%), carbohydrate content (54.758%), anthocyanin content (3.254 mg / 100g) and antioxidant activity 49.333%). Processing of fresh purple sweet potato into flour and cake results in decreased chemical composition and oxidant activity.